Дослідження характеристик польового кабеля у морській воді - Нокко, А. В. (ХНУРЭ, 2009)
This work studies the impact of Sea water on wave resistance, amplitude & phase frequencies characteristics of a communication cable.
Keywords: сети связи; дослідження характеристик польового кабеля